Revealing the regularities related to the professional activities of the air traffic controller of airport traffic control tower - Dzhuma, Liudmyla; Dmitriiev, Oleh; Lavrynenko, Oleksii; Soroka, Mykhailo (Technology audit and production reserves, 2021)
The object of research is the professional activity of an air traffic controller of the airport traffic control tower (henceforth Tower controller). The subject of research is the regularities revealing in this specialist activity in the performance of its work responsibility for the trainee reference model formation in the intelligent training system «ATC of Tower». One of the most problematic areas is the lack of training systems that would allow for independent training of these aviation specialists, whose knowledge assessment would be automatic and objective. The study used methods of analysis, combined timing, synthesis, statistical analysis and probabilistic modelling. The approach to data collection and analysis proposed as part of study made it possible to obtain an information flows circulation model at the Tower controller workplace and formalize the time characteristics of technological operations performed by it during the aircraft landing procedure. This is fundamentally important for the development of the trainee reference model of the intellectual training system, as well as for the implementation of the training mode and automatic objective assessment of the student’s knowledge and skills. The approbation obtained results of this approach of data collection and analysis make it possible to consider it an effective tool for obtaining objective information about the subject area of the Tower controller’s professional activity, which is a complex continuous-discrete stochastic dynamic control system with a mixed structure. In contrast to the formation of reference models existing approaches, the approach to collecting and analysing data proposed in the work makes it possible to develop a trainee reference model that more fully describes the Tower controller’s activities. Also, the proposed model reflects the order of actions, and when interacting with the trainee current model, it allows to implement objective (without an instructor) automatic assessment.